ZULFIYAKHANIM — THE VOICE OF WOMEN’S SPIRITUALITY IN UZBEK POETRY (SCIENCE TIME JOURNAL, 2026)
This article examines the creative legacy of Zulfiyakhanim as a prominent representative of Uzbek literature and a powerful voice of women’s spirituality. The study focuses on the philosophical depth of her poetry, the expression of moral values, and the portrayal of women’s strength and dignity. Special attention is given to the role of Zulfiyakhanim’s works in shaping spiritual consciousness and promoting ethical ideals in society.